Phase behavior of fatty carboxylic acids in n-heptane/water systems - Bravo, Bélgica; Sánchez, Jhoana; Chávez, Gerson; Cáceres, Ana; Ysambertt, Fredy; Márquez, Nelson (Ciencia)
The phase behavior of different fatty carboxylic acids (FA) in oil/water system was studied. The Winsor I-III-II transitions of ionized compounds were attained by varying the FA composition through the formulation scan. The effect of adding an alcohol in the system was study. The middle-phase volume decreases with the chain length and alcohol concentration. On the other hand, FA partition in biphasic systems was study. The partition isotherm is obtained plotting the decimal logarithm of the acid concentration in the oil and water phase. The intercept of this graph is related with the critical micellar concentration (cmc) of each fatty acid. It was observed that the cmc decreases with the chain length of FA.